Electrochemical, Spectroscopic and Morphological Characterization of Electrostatic Self-Assembled Hybrids of Tetracationic Phosphonium Porphyrins and Cdte Quantum Dots - Aguirre-Quintana, M; Aguirre-Quintana, M; Ruiz-Leon, D; Ruiz-Leon, D; Fuenzalida-Ortiz, F; Fuenzalida-Ortiz, F; Garcia-Sanhueza, C; Garcia-Sanhueza, C (Kluwer Academic Publishers, 2014)
Cationic porphyrins (i.e., [Ttolyl(P-(C6H5)3)4]4+, where Ttolyl = 5,10,15,20-tetrakis tolylporphyrin and CdTe capped with glutathione) were electrostatically self-assembled via a layer-by-layer methodology onto ITO electrodes and characterized by UV–Vis spectroscopy, cyclic voltammetry, electrochemical impedance spectroscopy (EIS) and SEM-EDX microscopy. Cyclic voltammetry studies of the cationic porphyrin [Ttolyl(P-(C6H5)3)4]4+ demonstrated its ability to absorb both glassy carbon and ITO electrodes. The electrochemical properties of the hybrid porphyrin/quantum dot films (i.e., ITO/{[Ttolyl(P-(C6H5)3)4]4+/CdTe}n, where n = 1–5 is the immersion step) were explored in buffer solutions in the presence or absence of the Fe(CN)6 3?/Fe(CN)6 4? redox couple at pH 7.0. The resistance to electron transfer determined by cyclic voltammetry and EIS is in agreement with the increase in the UV–Vis absorption of the material adsorbed onto the ITO surface for each newly assembled bilayer. The prepared bilayers exhibited an interesting homogeneous morphological distribution of CdTe quantum dots on the surface, which indicated the ability of [Ttolyl(P-(C6H5)3)4]4+ to organize CdTe nanoparticles on the ITO surface. EDX analysis of the bilayers confirmed the presence of Cd, Te, and S from the quantum dot. Linear sweep voltammetry indicated that ITO/{[Ttolyl(P-(C6H5)3)4]4+/CdTe}5 has oxygen reduction electrocatalytic properties and demonstrated a synergetic effect between the cationic porphyrin and the CdTe quantum dot. © 2014, Springer Science+Business Media Dordrecht.